Agricultural activities of the site «La Bóveda» and its impact on the water quality of runoff into the reservoir Sixto Durán Ballén - Espinel Pino, Verónica (2017)
The research realized in La Bóveda in Calceta (Ecuador) with the aim to determine the impact of the agriculture activities in La Bóveda where the quality of the water of run-offs to the reservoir Sixto Durán, to reach the accomplishment´s aim was proceeded to determine the agriculture activities of the community study, realizing topographic, hydrological maps and the use of soil, in addition you poll and cards to corroborate the obtained information, then there was realized the qualities´ valuation water for it there were realized three monitors which are included two in rainy weather and the other in dry one Damming Sixto Durán Ballén). The water quality valuation was done by means the methodology proposed Brown in 1970, which consists of 9 parameters included in Coliformes Fecales, Potential of Hydrogen, Biochemical Lawsuit of Oxygen, Nitrates, Phosphates, Change of Temperature, Turbidity, Occurred Diluted Totals, Oxygen Diluted, finally one proceeded to interrelate statistically the results obtained by means of the ICA depending on the physical, chemical and microbiological parameters of agreement to the permissible limits of the TULSMA, obtaining as result that the quality of the water in three realized monitoring is average for what it needs potabilizatión for the human consumption.